Characterization of iron nugget produced from iron ore concentrate in a microwave oven using a biomass-based reductant - Boyrazli, Mustafa; Ozturk, Elif Aranci; Benkli, Yunus Emre; Canbay, Canan Aksu (Consejo Superior Investigaciones Cientificas-Csic, 2023)
This study is concerned with the characterization of iron nuggets obtained from the reduction of an iron oxide concentrate in a microwave oven using a biomass-based reducing agent. In the experiments, the concentrate of iron ore consisting of hematite and magnetite minerals supplied from Elazig region and containing 67.29% Fe after enrichment, and as a reducing agent, tea plant wastes containing 94.68% C and 0.03% S after carbonization was used. Carbon required for the reduction of iron oxides to iron was stoichiometrically added to the concentrate with a grain size of-45 mu m after its basicity ratio was adjusted. The composite pellets produced after the addition of reducing agent and flux (CaO) were subjected to reduction in a household microwave oven at different times. After the process, optimum (Fe3O4+Fe2O3)/C=1/4, basicity ratio (CaO+MgO)/(SiO2+Al2O3) =1.2 results were obtained. It was seen that the metallic part contained 96.6% Fe, 2.4% C after being separated from the slag and that the metallic phase was separated from the slag very easily. As a result of the microstructure investigations, it was found that the product obtained had similar properties to white cast iron properties.
Keywords: Biomass; Carbonized tea plant waste; Composite pellet; Iron nugget; Magnetite; Microwave reduc-tion